Coulomb stress evolution in a diffuse plate boundary: 1400 years of earthquakes in eastern California and western Nevada, USA. Issue 8 (8th August 2016) - Verdecchia, Alessandro; Carena, Sara
Abstract: Diffuse plate boundaries are characterized by deformation distributed over a wide area in a complex network of active faults and by relatively low strain rates. These characteristics make it difficult to understand the spatial and temporal distribution of seismicity. The area east of the Sierra Nevada, between longitudes 121°W and 116°W, is part of a diffuse plate boundary. At least 17 major surface‐rupturing earthquakes have happened here in the last 1400 years. Our purpose is to determine whether these events influence each other or whether they are randomly distributed in time and space. We model the evolution of coseismic and postseismic Coulomb failure stress changes (ΔCFS) produced by these earthquakes, and we also model interseismic stresses on the entire fault network. Our results show that 80% of the earthquake ruptures are located in areas of combined coseismic and postseismic ΔCFS ≥ 0.2 bar. This relationship is robust, as shown by the control tests that we carried out using random earthquake sequences. We also show that the Fish Lake Valley, Pyramid Lake, and Honey Lake faults have accumulated 45, 37, and 27 bars, respectively, of total ΔCFS (i.e., coseismic + postseismic + interseismic) in the last 1400 years. Such values are comparable to the average stress drop in a major earthquake, and these three faults may be therefore close to failure. Key Points: Spatial distribution of major earthquakes over 1400 years is not random Coulomb stress changes control the sequence of major earthquakes Several faults capable of Mw ≥ 7 earthquakes may be close to failure